2005
DOI: 10.1093/pcp/pci202
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Reduces Aluminum Toxicity by Preventing Oxidative Stress in the Roots of Cassia tora L.

Abstract: Nitric oxide (NO) as a key signaling molecule has been involved in mediation of various biotic and abiotic stress-induced physiological responses in plants. In the present study, we investigated the effect of NO on Cassia tora L. plants exposed to aluminum (Al). Plants pre-treated for 12 h with 0.4 mM sodium nitroprusside (SNP), an NO donor, and subsequently exposed to 10 microM Al treatment for 24 h exhibited significantly greater root elongation as compared with the plants without SNP treatment. The NO-promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
183
1
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(199 citation statements)
references
References 57 publications
9
183
1
6
Order By: Relevance
“…NO has been suggested to be involved in defense responses to biotic and abiotic stresses. It has been reported to exert a protective effect in response to drought stress (Shehab et al 2010), osmotic stress (Tan et al 2008), salt stress (Habib et al 2013;Kausar et al 2013), chilling stress (Liu et al 2011), heat stress (Hasanuzzaman et al 2012), ultraviolet-B radiation ) and heavy metals stress (Esim & Atici 2013;Jhanji et al 2012;Kumari et al 2010;Singh et al 2009;Wang & Yang 2005). Nonetheless there is little information on the effect of NO application on lead toxicity tolerance in plants.…”
Section: Introductionmentioning
confidence: 99%
“…NO has been suggested to be involved in defense responses to biotic and abiotic stresses. It has been reported to exert a protective effect in response to drought stress (Shehab et al 2010), osmotic stress (Tan et al 2008), salt stress (Habib et al 2013;Kausar et al 2013), chilling stress (Liu et al 2011), heat stress (Hasanuzzaman et al 2012), ultraviolet-B radiation ) and heavy metals stress (Esim & Atici 2013;Jhanji et al 2012;Kumari et al 2010;Singh et al 2009;Wang & Yang 2005). Nonetheless there is little information on the effect of NO application on lead toxicity tolerance in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the concentration of free radical scavengers by exogenous application could help in the detoxification of stress-induced free radical production (Velikova et al, 2000;Shalata and Neuman, 2001;Verma and Mishra, 2005;Wang et al, 2004a;Wang and Yang, 2005;Zhang et al, 2006). In this study, we have tested two antioxidant compounds, putrescine and nitric oxide donor sodium nitroprusside.…”
mentioning
confidence: 98%
“…NO has also been reported to act as a signal molecule; mediating responses to biotic and abiotic stresses in the plant kingdom and it appears to be present in most of the stress reactions (Gould et al, 2003). It has been reported to exert a protective effect in response to drought stress (Wang et al, 2004b), salt stress (Kopyra and Gwozdz, 2003;Zhao et al, 2004;Chen et al, 2004), heavy metal stress (Hsu and Kao, 2005;Wang and Yang, 2005) and UV radiation stress (Shi et al, 2005). However experimental evidence for NO as a signal molecule for oxidative metabolism under salt stress is still preliminary.…”
mentioning
confidence: 99%
“…In fact, nitric oxide could mediate several physiological and biochemical functions in plants through its role as a signaling molecule (Besson-Bard et al, 2008). Even though enough research evidence on as to how nitric oxide minimize the abiotic stress is yet to receive, several authors reported that nitric oxide is involved in regulating plant's response to salinity (Song et al, 2009), water deficit (Neill et al, 2002) and to Al toxicity (Wang and Yang, 2005).…”
Section: Role Of Nitric Oxide On Aluminum Toxicitymentioning
confidence: 99%
“…Al-induced inhibition of root growth was found to be prevented by nitric oxide in Oryza sativa (Marciano et al, 2010); Hibiscus moscheutos (Tian et al, 2007) Cassia tora (Wang and Yang, 2005), Phaseolus vulgaris (Wang et al, (2010) and Citrus grandis (Yang et al, 2012). Al-induced oxidative stress in roots was also reported to be minimized by nitric oxide in Phaseolus vulgaris (Wang et al, (2010) and Cassia tora (Wang and Yang, 2005), where the action of nitric oxide against root growth inhibition was found to be correlated with less Al accumulation in root apexes.…”
Section: Role Of Nitric Oxide On Aluminum Toxicitymentioning
confidence: 99%